2020
DOI: 10.21203/rs.3.rs-127241/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved Strategy for Jet-in-air Cell Sorting With High Purity, Yield, Viability and Genome Stability

Abstract: Background: The enrichment of viable cells is an essential step in single-cell sequencing for clinical and biotechnology research applications. A high-end jet-in-air sorter is a fluorescent-activated cell sorting sorter that ideally processes cells with high purity, yield and viability. We want to improve the strategy for jet-in-air cell sorting to get more effective cells, and ensure the downstream experiments. Method: In this study, to achieve high-purity, high-yield, high-viability cell sorting, we explored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…Stopping the dissociation process is ensured by diluting the Collagenase P in Wash solution (2% FBS in HBSS). It has been shown that adding FBS increases cell viability and the final number of cells after sorting18 .2. Using a round-shaped scalpel blade no.…”
mentioning
confidence: 99%
“…Stopping the dissociation process is ensured by diluting the Collagenase P in Wash solution (2% FBS in HBSS). It has been shown that adding FBS increases cell viability and the final number of cells after sorting18 .2. Using a round-shaped scalpel blade no.…”
mentioning
confidence: 99%